Utility of High‐Dose Corticosteroids in the Treatment of ACE‐Inhibitor–Induced Angioedema. (2nd September 2014) - Bangiyev, John N.; Kieu, Monica C. Q.; Ray, Amrita; Cavaliere, Salvatore; Amjad, Esmael H.
Abstract : Objectives: Airway compromise is a common and dangerous presenting sign of ACE‐inhibitor–induced angioedema (AIIA). After a definitive airway is obtained, there is minimal evidence‐based data for the effectiveness of commonly used medical intervention. While dosing protocols for the treatment of AIIA vary between institutions, they usually contain a corticosteroid, H1‐blocker, and an H‐2 blocker. The aims of the study were: (1) Define ACE‐inhibitor‐induced angioedema. (2) Describe common upper aerodigestive subsites of involvement. (3). Discuss the role of corticosteroids in the management of ACE‐inhibitor–induced angioedema. Methods: We retrospectively reviewed 200 patient charts from a tertiary care center with diagnosed AIIA to determine the effectiveness of medications utilized in AIIA treatment. These patients were all admitted to the intensive care unit for airway monitoring. The intervention group (n = 100) received high dose steroids, H‐1 and H‐2 blockers IV. The control group (n = 100) received low dose or no steroids with or without H‐1 and H‐2 blockers. Outcome measures included length of hospital stay, length of ICU stay, emergent airway intervention, surgical airway intervention, and time intubated. Results: Preliminary data analysis supports a role for high dose corticosteroids in shortening length of stay ( P <. 05) and decreasing surgical airway intervention ( P <. 03). There is a trend for corticosteroids in reducing time intubated. Conclusions: These findings indicate that there is a role for medical management of upper aerodigestive AIIA with corticosteroids. These findings may ultimately help with the delineation of a standard protocol for AIIA.